Polycultures, pastures and monocultures: Effects of land use intensity on wild bee diversity in tropical landscapes of southeastern Mexico. (August 2019) - Vides-Borrell, Eric; Porter-Bolland, Luciana; Ferguson, Bruce G.; Gasselin, Pierre; Vaca, Raúl; Valle-Mora, Javier; Vandame, Rémy
Abstract: The conservation of pollinator diversity is fundamental to maintaining sustainable agricultural systems and food security. Some agricultural systems support pollinator diversity, while others may lead to their decline. Previous studies have evaluated the impacts of agricultural intensification on pollinators in temperate climates regions, but in tropical regions these impacts have been evaluated by only very few studies. We conducted a study in southeastern Mexico, in order to understand the effects of three agricultural systems on bee diversity in a tropical landscape. We compared 18 sites at two different scales (plot scale and landscape scale). We found a link between agricultural system intensity level at the plot scale and forest proportion at the landscape scale: land use intensity was low at both scales in 7 polycultures, low at plot scale and high at landscape scale in 4 pastures, and high at both scales in 7 monocultures. We collected bees at all sites, and found an overall high bee richness, with a total of 127 species. Bee richness was compared across agricultural systems using diversity accumulation curves with iNEXT package. Both polycultures and pastures had significantly higher richness as monocultures. We constructed bee species guilds according to ecological and life-history traits (i.e. size, sociality and nesting) and found that whatever the trait considered, the species richness in the different agricultural systems was most often affected in the same way than the complete community richness. Our results show, for the first time in tropical conditions that agricultural systems with low-intensity farming practices and forested landscape allow the preservation of a significantly higher diversity of bees than agricultural systems with high-intensity farming practices and highly deforested landscape. Considering that bee diversity is key to maintaining crop productivity, these findings can help scientists, policy-makers, and community members design policies that support both agricultural production and biodiversity conservation in the tropics. Highlights: Novel research in a tropical regions evaluating the effects of different agricultural systems on bee community. Bee guilds by life history traits have very similar response to agricultural intensification than the complete bee community. Most bee guilds are affected in the same way than the complete community in terms of richness.